(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2026)
Armenia’s pronounced altitudinal zonation and ongoing climate aridization may change both crop phenology and phytopathological risks in cereal-growing areas. This study evaluates how landscape belts and recent climate trends affect the spatiotemporal distribution of risk for the main fungal diseases of winter wheat, including yellow rust, leaf rust, septoria tritici blotch, powdery mildew, and tan spot. To address this goal, stable cereal cultivation zones were identified, their phenological features were analyzed under different physical-geographical conditions, and risk maps were created for the selected pathogens. The results demonstrate that elevation is a key driver of phenological asynchrony. Warming and lower moisture availability are associated with faster seasonal development and a redistribution of disease risks: on average, risk decreases in low-mountain areas and increases in mid-mountain belts. These findings highlight the need for earlier, zone-prioritized phytosanitary monitoring.